Evaluasi Rencana Tata Ruang Wilayah Terhadap Sebaran Satwa Endemik Macaca Maura di Kabupaten Maros - Muh Khalil Jibran; Rudi Latief; Emil Salim Rasyidi (Fakultas Teknik Universitas Bosowa, 2022)
Abstract. The purpose of this study was to determine the suitability of the habitat of endemic animals in Maros Regency and provide recommendations from the results of the evaluation of the spatial plan for the preservation of the habitat of the endemic animals of Macaca Maura. One of the endemic animals on the island of Sulawesi is Macaca Maura. Macaca Maura or Monkey Dare is a short-tailed primate that looks like a monkey. Both are protected animals, whose existence is currently threatened. The development that has been carried out so far has changed environmental conditions, both the physical environment and the social environment. Human activities lead to a reduction in forest cover and resource availability, threatening animal populations especially the Macaca Maura. This study uses a mixed method research design using the Maximum Entropy model to determine the suitability of the habitat of the Macaca Maura animal. Providing direction to maintain the ecosystem function of the Macaca Maura endemic animal is very necessary so that its habitat is maintained and protected from all forms of threats that can damage the ecology and natural habitat of Macaca Maura.